Linking Gut Microbiota and Stereotypic Behavior of Endangered Species Under Ex Situ Conservation: First Evidence from Sun Bears - Xiaobing Chen; Wenqi Chen; Xinyu Guo; Sheng Zhang; Bo Xu; Hong Wu; Dapeng Zhao (Animals)
Integrative conservation research on animal behavior and nutritional health can contribute to the ex situ conservation of endangered species. Stereotypic behavior, a repetitive behavior without practical function, is associated with animal welfare in its manner and frequency for captive animals. Exploring the potential relationship between stereotypic behavior and internal factors, such as intestinal flora, could improve ex situ conservation, especially for endangered species. In this study, we analyzed the typical behavior characteristics of the endangered sun bears (Helarctos malayanus) under captive conditions based on the behavior sampling method. The seasonal and annual changes in the intestinal flora of H. malayanus in captivity were studied by 16S rDNA high-throughput sequencing technology based on non-invasive fecal sample collection. This study provides the first evidence of a potential association between the gut microbiota and stereotypic behavior characteristics of captive H. malayanus. The results can significantly improve our understanding of the stereotypical behavior of H. malayanus in captivity and contribute to the captive breeding and conservation efforts of this endangered species.